The HSP90 inhibitor NVP-AUY922 radiosensitizes by abrogation of homologous recombination resulting in mitotic entry with unresolved DNA damage. - Shane Zaidi; Martin McLaughlin; Shreerang A Bhide; Suzanne A Eccles; Paul Workman; Christopher M Nutting; Robert A Huddart; Kevin J Harrington (PLoS ONE)
Background Heat shock protein 90 (HSP90) is a molecular chaperone responsible for the conformational maintenance of a number of client proteins that play key roles in cell cycle arrest, DNA damage repair and apoptosis following radiation. HSP90 inhibitors exhibit antitumor activity by modulating the stabilisation and activation of HSP90 client proteins. We sought to evaluate NVP-AUY922, the most potent HSP90 inhibitor yet reported, in preclinical radiosensitization studies. Principal findings NVP-AUY922 potently radiosensitized cells in vitro at low nanomolar concentrations with a concurrent depletion of radioresistance-linked client proteins. Radiosensitization by NVP-AUY922 was verified for the first time in vivo in a human head and neck squamous cell carcinoma xenograft model in athymic mice, as measured by delayed tumor growth and increased surrogate end-point survival (p = <0.0001). NVP-AUY922 was shown to ubiquitously inhibit resolution of dsDNA damage repair correlating to delayed Rad51 foci formation in all cell lines tested. Additionally, NVP-AUY922 induced a stalled mitotic phenotype, in a cell line-dependent manner, in HeLa and HN5 cell lines irrespective of radiation exposure. Cell cycle analysis indicated that NVP-AUY922 induced aberrant mitotic entry in all cell lines tested in the presence of radiation-induced DNA damage due to ubiquitous CHK1 depletion, but resultant downstream cell cycle effects were cell line dependent. Conclusions These results identify NVP-AUY922 as the most potent HSP90-mediated radiosensitizer yet reported in vitro, and for the first time validate it in a clinically relevant in vivo model. Mechanistic analysis at clinically achievable concentrations demonstrated that radiosensitization is mediated by the combinatorial inhibition of cell growth and survival pathways, ubiquitous delay in Rad51-mediated homologous recombination and CHK1-mediated G(2)/M arrest, but that the contribution of cell cycle perturbation to radiosensitization may be cell line specific.